xy over yx can be simplified to 1. 2x over 2y can be simplified to x over y. So the final step would be to simplify 1 divided by x over y, which would just be 1 multiplied by y over x. Answer: y/x (y over x)
6x-2y
0
-4(7x-3y-z)-(-6)(9x-z+2)
the answer to this problem is -2x^2y^2
Let's simplify it ... (4y-2x) = 0 = (2y -x ) = 0 2y = x y = x/2 Yes, it is linear.
6x-2x-6xy-2x-2y4x-2y=2x-2y-14xy
6x-2y
0
-4(7x-3y-z)-(-6)(9x-z+2)
the answer to this problem is -2x^2y^2
(5x -3x) (2y +8y) 2x + 10y
Let's simplify it ... (4y-2x) = 0 = (2y -x ) = 0 2y = x y = x/2 Yes, it is linear.
3x-2y+9+9y-x = 2x+7y+9
It is 16y+23x simplified
(2x)(2y) is the exact same as (2)(x)(2)(y) since they are all multiplication, which can be rearranged in any order, so this is also the same as (2)(2)(x)(y), which is the same as (4)(x)(y), so in the end: (2x)(2y)=4xy
-2x=2y+5 +2x -2y -2y=2x+5 /-2 y=-1/1+2.5
Any pair of numbers where the 'y' is 5 more than the 'x'. There are an infinite number of suitable pairs. 2y-2x=10 2y-2x+2x=10+2x 2y=2x+10 divide both side by 2. y=x+5